Quality of fresh and stored mares’ milk - Grażyna Czyżak-Runowska; Jacek Wójtowski; Alicja Niewiadomska; Maria Markiewicz-Keszycka (Mljekarstvo)
Mares’ milk is characterised by unique nutritional profile. In this study, the microbiological analysis of mares’ milk was performed. The presence of total bacteria, total lactic bacteria, Lactobacillus spp., Streptococcus lactis, Salmonella spp. and coliforms was investigated. Moreover, the influence of refrigerated and frozen storage on the total bacteria count, vitamin C, acidity and colour of milk was examined. Pathogenic Salmonella spp. and coliforms were not detected in the raw milk. It was revealed that mares’ milk can be stored for 72 hours under refrigeration at a temperature of +4 °C without reducing its microbiological quality. Most of the physicochemical properties remained unchanged, while colour measurements demonstrated a change in b* value after 48 h of refrigerated storage. Vitamin C content remained relatively stable during a week-long storage. Freezing of milk improved its microbiological status and caused significant changes in all colour components (L*, a*, b*). The obtained results demonstrated that mares’ milk had a high microbiological quality, favourable chemical composition and high vitamin C content which make this product a valuable potential component of functional foods.